Adsorpsi Pestisida Organofosfat Menggunakan Karbon Aktif : Studi Literatur - Hendrajaya, Glenn Lucas; Sururi, Mohamad Rangga; Nurjayati, Ratih (Journal Serambi Engineering, 2023)
Organophosphate (OP) pesticides are one of the pesticides with the widest and most widespread use in the world. Excessive use of agricultural land can have a negative impact on humans and the environment. One of the alternative methods that can be used to reduce OP in the environment is adsorption using activated carbon (KA). KA has been proven to be able to deal with various hazardous substances in the environment, including pesticides. This paper aims to look at KA’s capabilities and obstacles in adsorbing OP. The results of this review show that the adsorption ability of KA on OP depends on environmental temperature and pH. At optimum temperature, OP removal can reach 99.3%, while at optimum pH, KA’s adsorption capacity can be higher up to 68.15 mg/g. Other factors such as environmental characteristics, characteristics of the train used, and target adsorbate (OP) are still challenges for future research before its application in the agricultural environment.